Research on the reform of business analytics course in digital era with big data——taking “Python programming for economics and finance” as an example - LYU Yiqing; WU Yunfeng (大数据)
In the digital age, business analytics courses require teaching reforms that align with contemporary developments, particularly the integration of emerging technologies (such as Python programming and big data analysis) into the curriculum. This paper, focusing on the course "Python programming for economics and finance", finds the probelm of existing courses, including overly theoretical content, the singleness of assessment methods and inadequate cultivation of students' comprehensive application abilities. A series of reform measures are implemented, including curriculum content updates and innovative teaching methods. Comparisons between pre-and-post reform questionnaires and assessments reveal that these measures effectively enhance students' programming and problem-solving abilities, indicating the success of this educational reform and providing valuable insights for related research.